Manfaat Pijat Abdomen Bayi Usia 6-12 Bulan terhadap Konstipasi di Klinik Azzahra Nurfalah Kecamatan Cikarang Utara Kabupaten Bekasi - Wiwit Desi Intarti; Lina Karlina; Renince Siregar (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Constipation is a condition that is often found in children, constipation is a symptom of difficult bowel movements which is characterized by the consistency of hard stools, large size, and decreased frequency of bowel movements. Based on pathophysiology, constipation is classified into constipation due to organic disorders and functional constipation. The prevalence of constipation in children is estimated at 0.3% - 8%. The purpose of knowing the benefits of Abdomen Massage for Infants aged 6-12 Months Against Constipation at the Azzahra Nurfalah Clinic, Kec. North Cikarang, Bekasi Regency in 2023. Using an analytical method with a Quasi-Experimental research design with a pretest-posttest control group design. The population in this study were infants aged 6-12 months with constipation in the Azahra Nurfalah Clinic area with a total population of 30 respondents, the sample in this study was 30 respondents, 15 respondents had abdominal massage and 15 respondents did not have massage using a sampling technique. in total sampling. Data collection techniques used the division and filling out of checklists and questionnaires and were analyzed using the Independent T-Test test. Based on the results of the Independent T-Test test, a significant value of 0.000 was obtained, which means p <0.05, so it can be concluded that there is a significant benefit between abdominal massage for babies aged 6-12 months for constipation at the Azzahra Nurfalah Clinic, Kec. North Cikarang, Bekasi Regency in 2023. It is hoped that this research can be used to increase knowledge of the benefits of infant massage, namely making baby muscles stronger, increasing their immunity, reducing pain, and promoting defecation.